Pengaruh Green Accounting dan Media Exposure Terhadap Profitabilitas pada Perusahaan Tambang - Ika Din Rachmawati; Hayu Wikan Kinasih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of green accounting and media exposure on the profitability of mining companies listed on the Indonesia Stock Exchange. The background of this research is based on the importance of implementing environmental accounting and public information disclosure in improving corporate financial performance amid increasing sustainability demands. The research employs a quantitative method with a multiple linear regression approach. Data were obtained from annual reports of companies for the 2020–2024 period, selected using a purposive sampling method. The results show that green accounting and media exposure have a positive and significant effect on profitability. This indicates that the better a company manages environmental costs and enhances information transparency through media exposure, the higher its profitability level. However, the contribution of both independent variables is only 40%, while the remaining 60% is influenced by other factors not included in this study. This research is expected to serve as a reference for companies to strengthen their sustainability and transparency strategies to achieve optimal financial performance.